Desafios na publicação científica. - Volpato, Gilson Luiz; de Freitas, Eliane Gonçalves (FapUNIFESP (SciELO), 2003)
We discuss the main problems which make a scientific text difficult to find, to be read or to be accepted by readers. A scientific text is considered a logical argument. Therefore, methods, results and data from literature are premises supporting the conclusions of the work; and in the Introduction session, the justification corroborates the objective of the study. This conception makes the text a hermetically coherent structure where only the necessary data should be included (some controversy is still pertinent). In a second step, we show formal mistakes in scientific writing which make texts less attractive. Thus, we give examples of errors or inadequacy of formal aspects of presenting titles, abstracts, results (figures and tables), and grammar mistakes in Portuguese (but also valid for English grammar). After that, we emphasize the need for writing in international language (English) and for publication in periodicals with international impact on the scientific community. Finally, considerations to improve the Brazilian periodicals in the biological area are presented.
Challenge in scientific publication
Keywords: publication; publishing; research; standard; writing; Periodicals; Publishing; Research; Writing